2016
DOI: 10.1039/c6nr02669a
|View full text |Cite
|
Sign up to set email alerts
|

The origin of emissive states of carbon nanoparticles derived from ensemble-averaged and single-molecular studies

Abstract: At present, there is no consensus understanding on the origin of photoluminescence of carbon nanoparticles, particularly the so-called carbon dots. Providing comparative analysis of spectroscopic studies in solution and on a single-molecular level, we demonstrate that these particles behave collectively as fixed single dipoles and probably are the quantum emitter entities. Their spectral and lifetime heterogeneity in solutions is explained by variation of the local chemical environment within and around lumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
116
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(120 citation statements)
references
References 130 publications
4
116
0
Order By: Relevance
“…[10,13,14] The emission tunability has been most prominently ascribed to selective excitation of subsets of CDs within the CD ensemble. [15][16][17]32] Indeed, multiple studies have shown that it is possible to tune the emission by using different types of CDs that are themselves excitation independent. [18][19][20] On the other hand, Pan et al [11] and Fu et al [21] have suggested that different emission sites within individual CDs are responsible for excitation-dependent emission.…”
mentioning
confidence: 99%
“…[10,13,14] The emission tunability has been most prominently ascribed to selective excitation of subsets of CDs within the CD ensemble. [15][16][17]32] Indeed, multiple studies have shown that it is possible to tune the emission by using different types of CDs that are themselves excitation independent. [18][19][20] On the other hand, Pan et al [11] and Fu et al [21] have suggested that different emission sites within individual CDs are responsible for excitation-dependent emission.…”
mentioning
confidence: 99%
“…In Figure 4, the decay kinetics of C-dots emission bands are reported, along with their best fitting curves. The function used to fit the kinetics is a stretched exponential f (t) = A·e −((t/τ) b ) where is the fluorescence lifetime and b is the stretching parameter, which quantifies the degree of inhomogeneity of the emissive ensemble, due to the large dot-to-dot fluctuations observed for C-dots [26,29]. Excluding the case of C-dots in the presence of 100 mM iodide, the data in Figure 4 show that all the measured kinetics are identical within experimental uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…The essence of this phenomenon has been the most obscure of the CND features to date, and numerous efforts have been made to truly understand the physical basis and factors that may be involved and effect the optical properties of CNDs. However, there are several factors that hamper achieving a unified theory for the origin of CNDs emission: (i) inherent heterogeneity of CNDs due to the use of numerous precursors and approaches; (ii) uncertainty and complexity of functional and molecular groups on the surface induced during the synthesis process through different reaction pathways; and (iii) difficulties in the assessment of influence of size and surface chemicals on the optical properties due to lack of means for independent control of size and surface chemistry …”
Section: Introductionmentioning
confidence: 99%
“…These mentioned instances suggested that PL from CNDs should not be attributed to the particle as a whole (as for QDs), but to individual emitters within, and to communication between them . A single or a number of different emitters within an individual particle could exist, and there may be several excitation traps that could emit in parallel . The properties of such integrated systems are not always additive, or equal to the sum of the properties of their components .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation